Promoting Ethnocultural Traditions Through Sodoran Dance Learning - Trisakti, Trisakti; Juwariyah, Anik; abida, Fithriyah inda (Gelar: Jurnal Seni Budaya, 2022)
This research aims to reveal the nature of ethnocultural of Tenggerese people through Sodoran dance learning. Efforts to disseminate dance to students through creation and performance activities will increase their appreciation for the arts and culture of the community. Learning dance is one of the ways to preserve and transmit ethno-cultural traditions. This enhances the interest of the younger generation in gaining a deeper understanding of their culture, as well as the preservation and development of culture. This study used a qualitative method with a pedagogic approach. Sources of research data include: (1) Resource persons or people who are directly or indirectly involved in the dance learning process; (2) The dance learning process includes dance materials, teacher abilities, student behavior, and environmental resources. Data collection techniques are carried out through literature study, observation, and interviews. The result shows that through the learning process of Sodoran dance, students are able to appreciate the message contained within the dance and experience the cultural values that are embodied in Sodoran dance. This activity escalates their awareness to the outlook and culture of Tenggerese people.